Non-Linear Clumped Isotopes from DIC Endmember Mixing and Kinetic Isotope Fractionation in High pH Anthropogenic Tufa - Holdsworth,C; MacDonald,J; John,C (Minerals, 2022)
Clumped isotope values (Δ47) of carbonates forming in high pH conditions do not correspond to mineral precipitation temperatures due to certain effects including kinetic isotope fractionation and dissolved inorganic carbon (DIC) endmember mixing. Field-based archives of these carbonate environments are needed to evaluate and quantify these effects accurately. In this study, we measure the clumped isotope values of anthropogenic carbonates for the first time. Tufa layers were analyzed from samples precipitating in a high pH (>10) stream that drains a major slag heap in north east England. Δ47 values are 0.044‰–0.183‰ higher than expected equilibrium values. Non-linear distribution of clumped isotope data is diagnostic of DIC endmember mixing, rather than partial equilibration of DIC. Episodic dilution of hydroxide-rich stream waters by equilibrated rainfall surface runoff provides the mechanism by which mixing occurs. Δ47 values are ~0.010‰–0.145‰ higher than linear clumped isotope mixing profiles, suggesting that the majority of Δ47 increase results from a combination of endmember non-linear mixing effects and an atmosphere-hydroxide sourcing of DIC. The diagnostic trends and variation in clumped isotope values present in these results demonstrates the potential of anthropogenic carbonate systems as a useful archive for studying and quantifying kinetic effects in clumped isotopes.